The role of socio-demographics in the consciousness of sustainable consumption and the behaviour of young consumer - Szulc-Obłoza, Agnieszka; Haffer, Rafał; Pietrzak, Michał Bernard (Publishing House of Wroclaw University of Economics and Business, 2025)
Aim: This study investigated how the consciousness of sustainable consumption affects each of the consumption phases in terms of the different socio-demographic features of young consumers. Methodology: To achieve the aim of this study, the structural equation modelling (SEM) was applied. The research data were obtained through a computer assisted web interview (CAWI). Results: The results revealed not only that the consciousness of sustainable consumption has a signi-ficant effect on all three sustainable consumption phases, but also that socio-economic characteristics influence the strength of these relationships. Implications and recommendations: The conclusions may be helpful to stakeholders involved in sustainable supply chains, and to institutions involved in the education and promotion of sustainable behaviour. Originality/value: This study was the first to explore how the consciousness of sustainable consumption influences all stages of consumption among young consumers.
Argumenta Oeconomica, 2025, Nr 1 (54), s. 154-169
Keywords: consciousness of sustainable consumption; sustainable consumption; sustainable consumer; sustainable behaviour; young consumers